Territorial inequalities: depopulation and local development policies in the Portuguese rural world - Almeida, M. A. P. (Ager: Revista de estudios sobre despoblación y desarrollo rural, 2017)
The Portuguese rural world no longer resembles the one described in the literature, mostly because people no longer live or work there. Farmers became brand managers and tour hosts, workers were replaced by machines and intensive farming shoved entire populations to urban areas. With depopulation, the agrarian landscape has been transformed into a place for leisure or nature preservation. How are the remains of the rural being addressed by the few who still believe in life outside the big cities? What is the role of local government and its leaders in the sustainable development of the territory and its dynamic? All over the country, and particularly in rural areas, there is an urgent need to attract people and investment to fight depopulation and unemployment. What are the differences between projects for urban and rural municipalities? Political and economic strategies of municipalities and private entrepreneurs are analyzed and compared.